In vitro antibacterial activity of markhamiastipulata (wall.) Seem.Leaf extracts against selected gram-positive and Gram-negative bacteria - ANIMESH MAJI; PRIYANKA CHATTERJEE; SWASTIKA BANERJEE; SUMITA MONDAL; MOUMITA CHATTERJEE (International Journal of Pharma and Bio Sciences, 2018)
The present study focuses on the antibacterial potential of mature leaves of Markhamia stipulata (Wall.) Seem., which contribute towards the discovery of ‘green-antibacterial drugs’ for ensuring human health which was preliminarily fulfilled through assessment of the activity of mature leaves extract. The antibacterial activity was assessed using agar disc diffusion method. Best result was obtained with ethanolic leaf-extract against Pseudomonas aeruginosa whereas no antibacterial activity was observed against Escherichia coli. FT-IR analysis reveals the presence of various secondary metabolites. Hence, the plant can be used to discover bioactive natural products which lead to development of new antibacterial drugs by pharmaceuticals.